Changing epistemic beliefs? An exploratory study of cognition among prospective history teacher (Revista Tempo e Argumento, 2014)
This study explores changing epistemic beliefs in the history domain among 18 prospective history teachers. Drawing data from these college undergraduate history majors who were considering teaching careers, the study traces out an exploration of how epistemic beliefs may change at this crucial developmental point. A likert-scale instrument served as a primary data-gathering tool and it was administered in a pre-post, design.  Observational and interview data augmented the scale data.  A university-based course served as an educational vehicle designed to influence epistemic beliefs.  The results among the prospective teachers were mixed.  Some students’ epistemic beliefs remained unaffected by the course, while others changed, some quite dramatically.  Reasons for varied influences are the subject of the discussion.  Implications of the results are also considered.Keywords: Epistemic Knowledge; Historical Thinking; History Teaching; Prospective Teachers.